Improving Student Focus by Implementing Brain Gym Exercises Before Lessons - Prodyanatasari, Arshy (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
Learning concentration is a critical factor in students' academic success. However, many students struggle to maintain focus during the learning process. This study examined the effect of Brain Gym on concentration among third-grade students at SDN Bandar Lor 1, Kediri City. Using a quasi-experimental pretest–posttest control group design, 26 students were equally divided into experimental and control groups. The experimental group practiced Brain Gym® for ten minutes before lessons over four weeks, while the control group followed regular classroom routines. Concentration was measured through paper-based tests, observations, and questionnaires, including the Image Difference Test, Number Concentration Test, Word Arrangement Test, and Visual Memory Test. The results revealed that both groups were comparable at pretest (M = 28.62 control; M = 29.92 experimental). At posttest, the control group showed a small, non-significant increase (M = 32.08, p = 0.072), while the experimental group demonstrated a highly significant improvement (M = 53.38, p < 0.001) with a large gain score of 23.46 and effect size d = 3.12. These findings indicate that Brain Gym is an effective, low-cost, and practical classroom intervention that enhances concentration and supports learning readiness.